Politics of demography and urban space in ‘the land of prophets’: Israeli-Palestinian conflict and occupation policy - Yamamoto, Kensuke (Penerbit Universiti Kebangsaan Malaysia, 2017)
This article aims to analyze the present condition of the Israeli-Palestinian conflict by focusing on demography and space, in particular the urban space of the sacred cities, and examine the relationship between these two issues in the conflict. Obviously, demography and space are indivisible factors of Israeli-Palestinian conflict. At the national level, it concerns the demarcation between Israel and Palestine, and at the city level, urban space is a tying node of the politics of demography and space. Particularly, the conflict in the urban space of sacred city, the legitimacy of existence is contended. In such a case, even at the level of representation, demography and space have great deal of importance to decide how the conflict develops. So, demography and space are important both at national and city level, this might be an element to link between the macro and micro level of Israeli-Palestinian conflict.